2013 10th Working Conference on Mining Software Repositories (MSR) 2013
DOI: 10.1109/msr.2013.6624011
|View full text |Cite
|
Sign up to set email alerts
|

A study of innovation diffusion through link sharing on stack overflow

Abstract: Abstract-It is poorly understood how developers discover and adopt software development innovations such as tools, libraries, frameworks, or web sites that support developers. Yet, being aware of and choosing appropriate tools and components can have a significant impact on the outcome of a software project. In our study, we investigate link sharing on Stack Overflow to gain insights into how software developers discover and disseminate innovations.We find that link sharing is a significant phenomenon on Stack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 4 publications
3
21
0
1
Order By: Relevance
“…Their work proved the importance of effective knowledge management and sharing in software development. Gómez et al [25] focus on SO and studied the knowledge sharing in it. They found that SO plays an import role in software innovation dissemination.…”
Section: Related Workmentioning
confidence: 99%
“…Their work proved the importance of effective knowledge management and sharing in software development. Gómez et al [25] focus on SO and studied the knowledge sharing in it. They found that SO plays an import role in software innovation dissemination.…”
Section: Related Workmentioning
confidence: 99%
“…These internal links, which connect related posts that focus on similar or related questions, form inter-connected knowledge graph [14]. In Android Issue Tracker we can see that there are also links refer to related issues.…”
Section: Citation-graph Based Clusteringmentioning
confidence: 99%
“…Their work proved the importance of effective knowledge management and sharing in software development. Gómez et al [14] focus on SO and studied the knowledge sharing in it. They found that SO plays an import role in software innovation dissemination.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, Stack Overflow has attracted increasing attention from different research communities like software engineering, human computer interaction, social computing and data mining [6,9,10,21,22]. Researchers have mined the Stack Overflow knowledge-base to extract interesting and unique insights like API usage obstacles, innovation diffusion via URL link sharing,mobile development issues and programming topic trends [9,13,18,25]. Questions on Stack Overflow have received focused attention from researchers.…”
Section: Related Workmentioning
confidence: 99%